Biomimetic and biohybrid systems : 6th International Conference, Living Machines 2017, Stanford, CA, USA, July 26-28, 2017, Proceedings /: 6th International Conference, Living Machines 2017, Stanford, CA, USA, July 26-28, 2017, Proceedings. (2017) - Unknown
No abstract available